THE APPLICATION OF RCRR (READ, COVER, REMEMBER, RETELL) STRATEGY IN TEACHING READING DESCRIPTIVE TEXT TO THE EIGHTH GRADE STUDENTS OF STATE JUNIOR HIGH SCHOOL 50 PALEMBANG - Djunaidi Djunaidi (Esteem Journal of English Education Study Programme, 2019)
The main problem of this research was, “is it effective to apply RCRR (Read, Cover, Remember, Retell) Strategy in teaching reading descriptive text to the eighth grade students of state Junior High School 50 of  Palembang? This study was conducted to find out whether or not is it effective to apply RCRR strategy in teaching reading descriptive text entitle Borobudur Temple and Lake Toba to the eighth grade students of state Junior High School 50 of Palembang. This research was pre-experimental method with one group pretest-postetst design. The Population and sample of this research was eighth grade students at State Junior High School 50 of Palembang which consisted of 35 students. It was taken by using cluster random sampling method. The data were collected by using written test. The results of this research reveals, the average of the students’in pre-test was 59.85 while the students’ average score in the post-test was 78,14. The result of matched t-test calculation was 9.8 and it was higher than 1.691 as the critical value with 0.05 % significance level one tailed testing with df 34. It could be concluded that the application of RCRR (Read, Cover, Remember, Retell) Strategy to the eighth grade students of Junior High School 50 of Palembang was effective.